اثر متغيرات مالية و نقدية على التضخم: دراسة لبلدان نامية مختارة مع الإشارة الى العراق للمدة 1985-2000 - د. هاشم محمد عبدالله العركوب (PROSPECTIVE RESEARCHES, 2006)
This study presents an explanation to the nature of controversy among the three economical schools: The Keynesic, Monetary and Structural to define the phenomenon of inflation and show the factors which to such extent took part in their growth. More ever, the study aims at showing and limiting the trends of some of financial and monetary changes (from 1985 to 2000). The study also aims at acquainting to the changes under gone an the variables through the period understudy. It also tries to give explanations to these changes which greatly affect raising the ranges of inflation in the countries understudy. Then, the hypothesis adopted has been proved to betrue because of the increase in the ranges of governmental expenditure budget deficit and monitory expansion which effect increasing in the levels of inflation in the countries understudy.